Oral microbiota and metabolites: key players in oral health and disorder, and microbiota-based therapies - Bostanghadiri, Narjess; Kouhzad, Mobina; Taki, Elahe; Elahi, Zahra; Khoshbayan, Amin; Navidifar, Tahereh; Darban-Sarokhalil, Davood (Frontiers in Microbiology, 2024)
The review aimed to investigate the diversity of oral microbiota and its influencing factors, as well as the association of oral microbiota with oral health and the possible effects of dysbiosis and oral disorder. The oral cavity harbors a substantial microbial burden, which is particularly notable compared to other organs within the human body. In usual situations, the microbiota exists in a state of equilibrium; however, when this balance is disturbed, a multitude of complications arise.Dental caries, a prevalent issue in the oral cavity, is primarily caused by the colonization and activity of bacteria, particularly streptococci. Furthermore, this environment also houses other pathogenic bacteria that are associated with the onset of gingival, periapical, and periodontal diseases, as well as oral cancer. Various strategies have been employed to prevent, control, and treat these disorders. Recently, techniques utilizing microbiota, like probiotics, microbiota transplantation, and the replacement of oral pathogens, have caught the eye. This extensive examination seeks to offer a general view of the oral microbiota and their metabolites concerning oral health and disease, and also the resilience of the microbiota, and the techniques used for the prevention, control, and treatment of disorders in this specific area.